095 Remyelination in people with MS due to an RXR agonist is age-dependent. Issue 6 (27th May 2022) - McMurran, Christopher; Mukherjee, Trisha; William Brown, J; Michell, Andrew; Coles, Alasdair; Cunniffe, Nick
Abstract : Remyelination is a promising strategy to prevent axonal degeneration and progressive disability in people with multiple sclerosis (MS). In animal models, remyelination becomes inefficient with advancing age and much preclinical research is focused on interventions to reverse cellular hallmarks of ageing in remyelinat- ing lesions. However, there is currently limited evidence that human remyelination also declines with age. We investigated the effect of patient age on treatment response among participants of the CCMR One trial (ISRCTN14265371 ): a double-blind, placebo-controlled phase 2a study (n=52) that demonstrated the ability of bexarotene, a retinoid-X receptor agonist, to promote remyelination in people aged 25–50 with relapsing remitting MS. For eyes with chronic optic neuropathy (baseline latency >118ms), bexarotene shortened the full-field visual-evoked potential P100 latency maximally in younger patients. The treatment effect diminished by approximately 0.5ms per year, such that older patients receiving bexarotene had a similar P100 latency change to controls. Furthermore, MRI scans of the same patients demonstrated an age-dependent treatment effect on lesion magnetisation transfer ratio, a radiological correlate of remyelination. These results provide evidence that bexarotene promotes remyelination best in younger patients, rein- forcing the need to address the age-associated decline in remyelination capacity to develop successful remyelinating therapies. cem73@cam.ac.uk|NIHR Bursary